Tingkat Adopsi Wanita Tani dalam Program Kawasan Rumah Pangan Lestari (KRPL) untuk Mendukung Diversikasi Pangan - Isnian, Sitti Nur (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
One indicator of the sustainability of a development program is determined by the level of adoption in a community. This study aims to assess the level of adoption of female farmers in the KRPL. The research location was in Jampaka village, Kulisusu District, North Buton Regency, which was selected purposively considering that the place was representative of the Kulisusu District, where the KRPL program is still actively running. The study 20 women farmers selected through the census. The study was conducted in March-December 2019 and was designed as a quantitative study using the percentage and linear regression methods. Dialysis data is descriptive qualitative. The results showed that the level of adoption of female farmers in the KRPL Program which included land management activities, nurseries, planting, maintenance, building studio houses, and harvesting and post-harvesting, was in the medium category which means the program provides benefits to the community and allows the sustainability of the program to support food diversification. For maximum results in optimizing the program’s benefits, discipline by the government (extension) is needed to assist Women Farmers in implementing the program. It is hoped that this research will become